Physiological and neuromuscular effects of an electronically accentuated eccentric knee extension training - Kasperek, P.; Thilo, E. J.; Babiel, S.; Ferrauti, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Studies have shown, that an accentuated eccentric strength straining comes along with an increased muscle damage and consequently with stronger concentric adaptations of strength (Brandenburg et. al., 2002). The aim of the present study was to define the most effective relation between concentric and eccentric loads concerning neuromuscular activity and physiological demands during an accentuated training with an electronically controlled knee extension machine. Methods: 20 athletes (n=10 males and 10 females, age 24.3±3.1 yrs) completed three different training protocols during three experimental days, each at least three days apart. The training was conducted on an electronically leg extension machine (Milon Industries®, Germany), with separately adjusted concentric and eccentric resistance. Protocol A was defined as a traditional strength endurance training (TST) with equal loads (20 % 1 RM) in the concentric and eccentric movements. Protocol B (ECC+) and protocol C (ECC++) consisted of reduced concentric (B 16, C 12 % 1RM) and an increased eccentric load (B 24, C 28 % 1RM). During each protocol eight sets of eight repetitions (7.5 s each and 1 min duration per set) followed by 30 s recovery were completed. Results: No differences were found for the mean heart rate (A 106±13, B 107±14, C 103±12 min-1) and perceived exertion (A 14±1, B 14±2, C 14±1). Mean oxygen consumption was significantly lower in Protocol C (A 8.4±2.4, B 8.4±1.6, C 7.5±1.8 ml·min/kg). M. vastus medialis activity tended to be higher during concentric contraction in A (A 0.19±0.11, B 0.14±0.06, C 0.13±0.04 mV) while no differences were found for the eccentric movements (A 0.15±0.07, B 0.14±0.04, C 0.14±0.04 mV). Neuromuscular activity decreased significantly during the second half of the eccentric movements in all protocols. Discussion: Results showed that an accentuated eccentric strength training comes along with an overall lower energy demand despite of a similar power output and does not increase neuromuscular activity as expected under the conditions of our study. These results may be attributed to a faster movement in case of eccentric overload.